SANKSI PIDANA TINDAK PIDANA PENGGELAPAN DALAM HUBUNGAN KERJA - Nurul Fadilah; Eriyantouw Wahid (Reformasi Hukum Trisakti, 2023)
Bagus Setianto committed the offense of embezzlement in working relationships by stealing money from product sales. The question posed in this essay is whether the perpetrator's conduct comply with article 374 of the Criminal Code and if the judge made the right choice in issuing a 2-year sentence. This study use normative research methodologies, analyzes qualitative data, uses secondary data, and uses deductive reasoning to reach findings. The findings revealed that Bagus Setianto had erred by abusing his position as supervisor. Specifically, the defendant had altered the assigned email address and embezzled money from product sales by repeatedly transferring it to his wife's account without getting permission from Pangansari Utama Food Distribution for his own use.